2012
DOI: 10.1007/s10067-012-2071-8
|View full text |Cite
|
Sign up to set email alerts
|

Appearance concern and depression in adolescent girls with systemic lupus erythematous

Abstract: To examine the relationship between physical appearance concern and psychological distress in female adolescent patients with systemic lupus erythematosus (SLE) was the aim of this study. A total of 84 adolescent SLE female patients and 80 age-matching healthy adolescents were evaluated for levels of appearance concern and a range of illness-specific measures to determine how these demographic and clinical variables were related to the dependent variable psychological distress. The Systemic Lupus Erythematosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 18 publications
2
38
0
1
Order By: Relevance
“…Both patients and staff reported acceptance of screening on qualitative surveys. Elevated CDI scores ($16) were found in 8% of the sample; moderate scores (10)(11)(12)(13)(14)(15) in 12% of the sample. Low risk scores were found in 80% of the sample.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Both patients and staff reported acceptance of screening on qualitative surveys. Elevated CDI scores ($16) were found in 8% of the sample; moderate scores (10)(11)(12)(13)(14)(15) in 12% of the sample. Low risk scores were found in 80% of the sample.…”
Section: Resultsmentioning
confidence: 91%
“…Up to 9.5% of the general population of adolescents are depressed, [8][9][10] and the rate is 2 to 3 times higher for adolescents with type 1 diabetes and other chronic health conditions. [11][12][13][14][15][16] When present, depression in adolescents with type 1 diabetes is associated with less frequent blood glucose monitoring (BGM), 17 higher HbA1c values, [18][19][20][21] and increased rates of diabetes-related hospitalizations. 22,23 All of these negative health outcomes are associated with higher risk of longterm complications from diabetes and consequent increase in medical care costs.…”
Section: Resultsmentioning
confidence: 99%
“…The etiology of depression and anxiety in pediatric SLE and MCTD patients is likely complex and related several factors including: the psychological stress of dealing with a chronic illness during adolescence [39]; inflammatory central nervous system (CNS) pathology related to SLE [40]; direct steroid CNS effects [41] and indirect steroid-related somatic effects (eg. appearance concern due to weight gain, acne and striae) [42], as well as; hereditary and environmental factors [16, 18, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the complex chronically ill children at freestanding children' s hospitals have a relatively high burden of mental health comorbidities, which is consistent with studies in chronically ill pediatric outpatients. [25][26][27][28][29] We also found that the most common comorbid mental health diagnoses differed between hospitals nationally and free-standing hospitals.…”
Section: Discussionmentioning
confidence: 57%